READING STRATEGY USE AMONG IRANIAN EFL LEARNERS ACROSS DIFFERENT PROFICIENCY LEVELS - Mirzapour, Fatemeh; Mozaheb, Mohammad Amin (European Scientific Journal, ESJ, 2015)
This study investigated the type and the frequency of the use of strategies in reading comprehension among Iranian EFL learners with varying proficiency levels, that is, Advanced versus Intermediate learners. It was hypothesized that there was no significant relationship between learners’ proficiency level and the type and the frequency of use of reading strategies. Sixty learners, aged 15-27, were selected from the intermediate and advanced EFL learners in Omid Language Center of Marand. Preliminary English Test (PET) and Original Survey of Reading Strategies (SORS) Questionnaire were used as the main data collection tools. The result reveals that there are differences between Intermediate and Advanced learners on the use of global and problem- solving strategies because Advanced learners use these strategies more than Intermediate learners. But there are no differences between Advanced and Intermediate learners on the use of support strategies. It is believed that the present study can have insightful implications for EFL learners and teachers.